Tour guiding in Zimbabwe: key issues and challenges - Nyahunzvi, Dzingai K.; Njerekai, Cleopas (Elsevier, 2016)
Although it is widely documented that tour guides can make or break a tour, there is limited research around the key issues and challenges facing the tour guiding profession, globally. Against this backdrop, this study brings to the fore the key issues and challenges facing Zimbabwe's tour guiding profession. Data for this study was collected through mainly semi-structured interviews that were held with a range of stakeholders. The multi-stakeholder approach adopted in this study aimed to capture emic views in line with prior research. Findings suggested a matrix of challenges that faced the tour guiding profession including lack of job security, low remuneration, a limited and expensive training curricular and low career development opportunities. Key among the paper's recommendations is that the depressed tourism environment obtaining in Zimbabwe among other constraints has to be addressed as a matter of urgency. The paper also indicates future research priorities.